The Dangerous Dissemination of Personal Data and Its Legal Consequences - Monaselidze, Nino (Journal of Law, 2025)
In recent years, hate speech and aggression on social media have increased worldwide. These developments are often accompanied by the publication of personal data and have led to a disturbing phenomenon within peaceful societies. During the protests in Georgia in 2024–2025, both law enforcement authorities and civil society activists circulated photos, names, and home addresses of individuals with dissenting opinions in open and closed chats, often with the intent to intimidate or harass them.[1] This contributed to both physical attacks and online harassment against the targeted individuals. Because much of the disseminated information involved publicly available data, such actions were not punishable under Georgian law and law enforcement authorities did not intervene. This legal gap in Georgian legislation could be addressed by drawing on Section 126a of the German Criminal Code (StGB), which was introduced in 2021 specifically to combat this type of behavior. [1] https://mtavari.tv/news/171574-aktsiis-darbevashi-monacile-modzalade [25.09.2025].